Predictors of important neurological causes of dizziness among patients presenting to the emergency department. Issue 7 (28th June 2010) - Cheung, C S K; Mak, P S K; Manley, K V; Lam, J M Y; Tsang, A Y L; Chan, H M S; Rainer, T H; Graham, C A
Abstract : Objectives: Dizziness is a common presenting complaint in the emergency department (ED). This prospective study describes the incidence, causes and outcome of ED patients presenting with dizziness and tries to identify predictors of central neurological causes of dizziness. Methods: Single-centre prospective observational study in a university teaching hospital ED in Hong Kong. All ED patients (≥18 years old) presenting with dizziness were recruited for 1 month. Symptoms, previous health, physical findings, diagnosis and disposition were recorded. The outcome at 3 months was evaluated using hospital records and telephone interviews. Follow-up was also performed at 55 months using computerised hospital records to identify patients with subsequent stroke and those who had died. Results: 413 adults (65% female, mean 57 years) were recruited. The incidence of dizziness was 3.6% (413/11 319). Nausea and/or vomiting (46%) and headache (20%) were the commonest associated findings. Hypertension (33%) was the commonest previous illness. Central neurological causes of dizziness were found in 6% (23/413) of patients. Age ≥65 years (OR=6.13, 95% CI 1.97 to 19.09), ataxia symptoms (OR=11.39, 95% CI 2.404 to 53.95), focal neurological symptoms (OR=11.78, 95% CI 1.61 to 86.29), and history of previous stroke (OR=3.89, 95% CI 1.12 to 13.46) and diabetes mellitus (OR=3.57, 95% CI 1.04 to 12.28) predicted central causes of dizziness. Conclusions: Most dizzy patients had benign causes. Several clinical factors favoured a diagnosis of central neurological causes of dizziness.